Pengembangan Modul Pembelajaran pada Pembuatan Macam-macam Kampuh di Fase E SMK Negeri 1 Sooko Mojokerto - Ulfatul Maf Ula; Ma’rifatun Nashikhah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Learning in phase E of SMK Negeri 1 Sooko Mojokerto contains elements of Basic Sewing Techniques (TDM), namely students can make various kinds of seam allowances. The obstacles experienced by students are that students find it difficult to create various kinds of seam allowances, because the practice made is more than 3 kinds and students often forget the process of making it, even the value obtained is still below the achievement of learning objectives (KKTP). One thing that can encourage students in learning in the classroom is that educators provide media in the form of learning modules aimed at learning guidelines that can be used by students. This research method uses R&D by implementing ADDIE which can have 5 stages including analysis, design, development, implementation and evaluation. The findings from the results of this learning module are based on the validator of materials and media which get an average of 3.48 which is declared feasible. The learning outcomes of students after implementing the module are achieved classically around 91% declared complete.